Improved high range resolution profiling of aircraft using stepped-frequency waveforms with an S-band phased array radar - French, A. (2006 IEEE Conference on Radar, 2006)
A signal processing scheme based upon stepped-frequency waveforms is presented which enables high range resolution (HRR) profiles of targets to be formed of potentially sub-meter resolution, and extent of several kilometers, using an S-band (/spl sim/3 GHz) radar system. This 'Hybrid' method is a significant improvement upon conventional ('Classical') HRR techniques, which have severely limited range unambiguous range extents. Successful aircraft trials and static experiments have been conducted using the MESAR2 phased array multifunction radar. Phased array time delay effects resulting from the reception of off-boresight target reflections were overcome without the need for calibration at every azimuth angle. Key application advantages are the potential to form high resolution range profiles of multiple target raids in an air defense scenario and extended threat clouds in ballistic missile defense.